QSAR MODELING OF 2-[CH(OH)X]-5,8-(OY)2 -1,4-NAPHTHOQUININES AGAINST L1210 CELLS USING MULTIPLE LINEAR REGRESSION - Ajeet .; Brajpal Singh; Vipul Kumar (Indonesian Journal of Pharmacy, 2012)
Quinones are present in many drugs such as anthracyclines, daunorubicin,  doxorubicin,  mitomycin,  mitoxantrones  and saintopin, which are used clinically in the therapy of solid cancers. The  cytotoxic  effects  of  these  quinone  are  mainly  due  to  the inhibition  of  DNA  topoisomerase-II.  It  is  the  necessity  to  develop the  1,4-Naphthoquinone  analogues  with  Cytotoxic  effect.  Here  2-[CH(OH)X]-5,8-(OY)2-1,4-Naphthoquinines  analogues  have  been used  to  correlate  the  cytotoxic  activity  with  the  Eccentric Connectivity index (ECI), Fragment Complexity (FC) and McGowan Volumes  (MG)  for  studying  the  Quantitative  Structure  Activity Relationship  (QSAR).  Correlation  may  be  an  adequate  predictive model  which  can  help  to  provide  guidance  in  designing  and subsequently  yielding  greatly  specific  compounds  that  may  have reduced  side  effects  and  improved  pharmacological  activities.  We have  used  Multiple  Linear  Regression  (MLR),  one  of  the  best methods for developing the  QSAR model. Results from this QSAR study  have  suggested  that  ECI,  FC  and  MG  are  the  important descriptors for cytotoxic activities of 1,4-Naphthoquinones against L1210  cells.  For  the  validation  of  the  developed  QSAR  model, statistical  analysis  such  as  data  point-descriptor  ratio,  fraction  of variance,  cross  validation  test,  standard  deviation,  quality  factor, Fischer’s test; and internal validation such as Y-randomization test have been performed and all the tests validated this QSAR model.Key  words:  1,4-Naphthoquinones,  QSAR,  Eccentric  connectivity  index, Fragment  complexity,  McGowan  Volume,  Multiple  Linear Regression